Assessing the scapholunate and lunotriquetral interosseous ligament in MR arthrography: Diagnostic advantages of paraxial reformatting. Issue 142 (September 2021) - Huflage, Henner; Luetkens, Karsten Sebastian; Conrads, Nora; Jakubietz, Michael Georg; Jakubietz, Rafael Gregor; Schmitt, Rainer; Goertz, Lukas; Pennig, Lenhard; Bley, Thorsten Alexander; Grunz, Jan-Peter
Highlights: SLIL and LTIL are the main stabilizers of the proximal carpal row. MR arthrography is the imaging standard for ligamentous injuries of the wrist. Superior ligament assessability is feasible with angulated anatomical reformations. Diagnostic accuracy for LTIL lesions improves with access to paraxial reformatting. Abstract: Purpose: The scapholunate (SLIL) and lunotriquetral interosseous ligament (LTIL) function as the main stabilizers of the proximal carpal row. Even with MR arthrography, component assessability is often limited in orthogonal standard planes due to their horseshoe-like shape and resulting partial volume effects. This study aims to investigate the diagnostic value of reformatting isotropic 3D sequences with respect to the anatomical orientation of the intrinsic carpal ligaments. Method: In 110 MR arthrograms of the wrist, we investigated the diagnostic accuracy of two radiologists (R1/R2) for SLIL and LTIL injuries in orthogonal standard planes vs. ancillary angulated reformatting of isotropic 3D dual echo steady state sequence. Component assessability and diagnostic confidence were compared between datasets. Results: The addition of paraxial reformations improved diagnostic accuracy for lesions of the palmar (R1: 0.87 vs. 0.93; R2: 0.86 vs. 0.93; all p < 0.05) and dorsal LTIL (R1: 0.85 vs. 0.93; R2: 0.82 vs. 0.90; all p < 0.05). No significant increase in accuracy could be ascertained for palmar (R1: 0.92 vs. 0.94, p = 0.50; R2: 0.86 vs. 0.92, p = 0.07) and dorsal (R1: 0.95 vs. 0.95, p = 1.00; R2: 0.90 vs. 0.94, p = 0.29) lesions of the SLIL. Interrater reliability was almost perfect with and without angulated planes for SLIL (κ = 0.88 vs. 0.82) and LTIL assessment (κ = 0.88 vs. 0.86). For the LTIL, observer confidence and component assessability were superior with anatomical reformations available (all p < 0.05). Conclusions: In contrast to SLIL injuries, diagnosis of LTIL lesions benefits from ancillary paraxial reformations of 3D sequences in MR wrist arthrography.